Geochemical and Petrographic Characterization of Marine-Continental Transitional Facies Shale (Qilian Basin, China): Origin of Organic Matter Input, Depositional Environments and Hydrocarbon Generation Potential - Wang, Guocang; Sun, Minzhuo; Yi, Zongwang; Zhou, Li; Ye, Jie; Tan, Heyong (Frontiers in Earth Science, 2021)
This study, for the first time, investigates the source, keroger pattern, evolution degree, sedimentary environment and evaluates the hydrocarbon generating ability of marine-continental transitional facies shale from the Ebao area of the Qilian Basin in western China. The organic-rich shales of the marine-continental transitional facies were subjected to TOC, rock pyrolysis, the biomarkers and kerogen microscopy analyses. The kerogen microscopy analyses indicated that the sample from ZK001 well and ZK2002 well had a mass of vitrinite and small number of exinite, so kerogen type was mainly humic. According to vitrinite reflectance, the organic matter was in the stage of maturity to high maturity. The organic analyses indicated that the shale samples possessed the features of the higher TOC and a mixed of terrestrial and marine sources and maturity to high maturity. These features were compatible with the characterized of kerogen microscopy characteristics. A lot of organic materials in the studied shales form ZK001 well and ZK2002 well could be because there were fine protection under salt lake facies and hypoxic marine environment. Therefore, the studied shales of marine-continental transitional facies shale had very good hydrocarbon generating ability as a result of the existence of a lot of high maturity organic materials of humic.